2021
DOI: 10.1002/jcla.24003
|View full text |Cite
|
Sign up to set email alerts
|

circCORO1C promotes the proliferation and metastasis of hepatocellular carcinoma by enhancing the expression of PD‐L1 through NF‐κB pathway

Abstract: Background: Circular RNA (circRNA) affects the occurrence and development of human cancers, but the specific mechanism of hepatocellular carcinoma (HCC) has not yet been fully understood. Methods: CircRNAs were determined by human circRNA array analysis and quantitative reverse transcription polymerase chain reaction (qRT-PCR). Cell viability, migration, invasion, and other indicators were used for cell function analysis. Knockdown and overexpression techniques were used to explore the mechanism of circCORO1C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…Wu и соавт. [352] исследовали онкогенный потенциал кольцевой РНК DLEU2 (circDLEU2), содержание микроРНК-496 и активируемой протеинкиназой циклического аденозинмонофосфата (цАМФ) каталитической субъединицы PRKACB микроРНК в опухолевых клетках ОМЛ. Установили, что уровень экспрессии кольцевой РНК circDLEU2 был повышен в тканях ОМЛ и способствовал пролиферации опухолевых клеток, при этом ингибировался клеточный апоптоз in vivo.…”
Section: острый миелоидный лейкозunclassified
See 1 more Smart Citation
“…Wu и соавт. [352] исследовали онкогенный потенциал кольцевой РНК DLEU2 (circDLEU2), содержание микроРНК-496 и активируемой протеинкиназой циклического аденозинмонофосфата (цАМФ) каталитической субъединицы PRKACB микроРНК в опухолевых клетках ОМЛ. Установили, что уровень экспрессии кольцевой РНК circDLEU2 был повышен в тканях ОМЛ и способствовал пролиферации опухолевых клеток, при этом ингибировался клеточный апоптоз in vivo.…”
Section: острый миелоидный лейкозunclassified
“…Кроме того, после дополнительных экспериментов было обнаружено, что повышенная экспрессия circDLEU2 существенно ингибирует экспрессию микроРНК-496, что способствует увеличению количества другой микроРНК. Это коллективное исследование показало, что повышенная экспрессия кольцевой РНК circDLEU2 усиливает развитие ОМЛ человека, за счет подавления микроРНК-496 и стимуляции экспрессии PRKACB микроРНК [352].…”
Section: острый миелоидный лейкозunclassified
“…In recent years, the effect of circRNAs mediated PD-L1 expression on the immune status of liver cancer has attracted much attention. Has-circ-0006852 (circCORO1C) promoted the development of HCC by activating the NF-κB signaling pathway, increasing the phosphorylation of P65, the expression of c-Myc, COX-2 and PD-L1 ( 158 ). Has-circ-0003288 acted as a miR-145 sponge and up-regulated PD-L1 expression through the PI3K/AKT signaling pathway, promoting EMT and HCC invasion ( 159 ).…”
Section: Expression Of Pd-l1 In Tumor Cellsmentioning
confidence: 99%
“…Multiple studies have shown that circRNAs are associated with the development and treatment of liver cancer. 52 Moreover, the activation of mTOR is considered to be an important event in the development of liver cancer. 53 CircC16orf62, hsa_circ_100,338, hsa_circ_0004001, hsa_circ_0004123, and hsa_circ_0075792 possess differential expression in HCC tissues and cells compared with adjacent normal tissues and cells and play the significant role of oncogenes when overexpressed in liver cancer.…”
Section: Digestive Systemmentioning
confidence: 99%
“…Nevertheless, drug resistance and distant metastasis are remarkable obstacles to liver cancer treatment. Multiple studies have shown that circRNAs are associated with the development and treatment of liver cancer 52 . Moreover, the activation of mTOR is considered to be an important event in the development of liver cancer 53 .…”
Section: Digestive Systemmentioning
confidence: 99%